2015
DOI: 10.5152/eurasianjmed.2015.43
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Mean Platelet Volume in Patients with Resistant Hypertension, Controlled Hypertension and Normotensives

Abstract: Objective: Patients with resistant hypertension are at increased risk for cardiovascular events. Mean platelet volume (MPV) is an accepted biomarker of platelet activation and considered as a risk factor for cardiovascular disease. The aim of this study was to determine whether MPV levels are higher in resistant hypertensive (RHTN) patients than in controlled hypertensive (CHTN) patients and healthy normotensive controls. Materials and Methods Results:The mean platelet volume levels were significantly higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
25
1
2

Year Published

2016
2016
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 29 publications
1
25
1
2
Order By: Relevance
“…However, the role of platelet activation in cardiovascular events has led us to speculate that it may be associated with hypertension. In fact, previous studies have found elevated MPV values in resistant hypertension 6 and non-dipper hypertension. 7 However, whether an elevated MPV can independently predict future risk for hypertension has not been noted in the literature.…”
Section: Introductionmentioning
confidence: 87%
“…However, the role of platelet activation in cardiovascular events has led us to speculate that it may be associated with hypertension. In fact, previous studies have found elevated MPV values in resistant hypertension 6 and non-dipper hypertension. 7 However, whether an elevated MPV can independently predict future risk for hypertension has not been noted in the literature.…”
Section: Introductionmentioning
confidence: 87%
“…Jalur NO memliki interaksi sinergistik dengan pembentukan/degradasi nukleotida siklik dan fosforilasi protein pada trombosit dan sel otot polos, yang mengatur fungsi kardiovaskular (tonus vaskular, inhibisi agregasi trombosit serta adhesi leukosit, dan pencegahan proliferasi sel otot polos). [8][9][10] Dalam beberapa tahun terakhir, neutrofilia dan lymphocytopenia relatif terbukti menjadi prediktor independen kematian pada pasien dengan gagal jantung akut. Selain itu, rasio neutrofil-ke-limfosit (NLR) diperkenalkan sebagai penanda potensial untuk menentukan inflamasi pada gangguan jantung dan nonjantung.…”
Section: Pendahuluanunclassified
“…[1923] Moreover, the use of antiplatelet management therapies in the high blood pressure, the platelets play a pivotal role in the pathogenesis of hypertension. [2427] Thus, assessments of platelet indices and their bioactivity may be of vital importance for monitoring the occurrence and progression of hypertension. Asgari et al [28] used the quadratic inference functions (QIFs) to determine the factors associated with obesity from the STEPS Survey in Iran.…”
Section: Introductionmentioning
confidence: 99%